Anemia at Discharge From the PICU: A Bicenter Descriptive Study. Issue 9 (September 2019) - Demaret, Pierre; Valla, Frédéric V.; Behal, Hélène; Mimouni, Yanis; Baudelet, Jean-Benoît; Karam, Oliver; Recher, Morgan; Duhamel, Alain; Tucci, Marisa; Javouhey, Etienne; Leteurtre, Stéphane
Abstract : Objective: To determine the prevalence and risk markers of anemia at PICU discharge. Design: Bicenter retrospective cohort study. Setting: Two multidisciplinary French PICUs. Patients: All children admitted during a 5-year period, staying in the PICU for at least 2 days, and for whom a hemoglobin was available at PICU discharge. Interventions: None. Measurements and Main Results: Patient, admission, and PICU stay characteristics were retrospectively collected in the electronic medical records of each participating PICU. Anemia was defined according to the World Health Organization criteria. Among the 3, 170 patients included for analysis, 1, 868 (58.9%) were anemic at discharge from PICU. The proportion of anemic children differed between age categories, whereas the median hemoglobin level did not exhibit significant variations according to age. After multivariate adjustment, anemia at PICU admission was the strongest predictor of anemia at PICU discharge, and the strength of this association varied according to age (interaction). Children anemic at PICU admission had a reduced risk of anemia at PICU discharge if transfused with RBCs during the PICU stay, if less than 6 months old, or if creatinine level at PICU admission was low. Children not anemic at PICU admission had an increased risk of anemia at PICU discharge if they were thrombocytopenic at PICU admission, if they had higher C -reactive protein levels, and if they received plasma transfusion, inotropic/vasopressor support, or mechanical ventilation during the PICU stay. Conclusions: Anemia is frequent after pediatric critical illness. Anemia status at PICU admission defines different subgroups of critically ill children with specific prevalence and risk markers of anemia at PICU discharge. Further studies are required to confirm our results, to better define anemia during pediatric critical illness, and to highlight the causes of post-PICU stay anemia, its course, and its association with post-PICU outcomes. Abstract : Supplemental Digital Content is available in the text.